Small is beautiful, but large is certified: A comparison between fisheries the Marine Stewardship Council (MSC) features in its promotional materials and MSC-certified fisheries - Le Manach, Frédéric; Jacquet, Jennifer L.; Bailey, Megan; Jouanneau, Charlène; Nouvian, Claire (PLOS ONE, 2020)
The Marine Stewardship Council (MSC) sets a standard by which sustainable fisheries can be assessed and eco-certified. It is one of the oldest and most well-known fisheries certifications, and an estimated 15% of global fish catch is MSC-certified. While the MSC is increasingly recognized by decision-makers as an indicator for fishery success, it is also criticized for weak standards and overly-lenient third-party certifiers. This gap between the standard’s reputation and its actual implementation could be a result of how the MSC markets and promotes its brand. Here we classify MSC-certified fisheries by gear type (i.e. active vs. passive) as well as by length of the vessels involved (i.e. large scale vs. small scale; with the division between the two occurring at 12 m in overall length). We compared the MSC-certified fisheries (until 31 December 2017) to 399 photographs the MSC used in promotional materials since 2009. Results show that fisheries involving small-scale vessels and passive gears were disproportionately represented in promotional materials: 64% of promotional photographs were of passive gears, although only 40% of MSC-certified fisheries and 17% of the overall catch were caught by passive gears from 2009–2017. Similarly, 49% of the photographs featured small-scale vessels, although just 20% of MSC-certified fisheries and 7% of the overall MSC-certified catch used small-scale vessels from 2009 to 2017. The MSC disproportionately features photographs of small-scale fisheries although the catch it certifies is overwhelmingly from industrial fisheries.